COMBATING SECURITY CHALLENGES IN THE NORTH-EAST OF NIGERIA: JUSTIFICATION FOR AN ANTI-TERRORISM COURT. (AUN INTERNATIONAL CONFERENCE, 2024)
The northeastern region of Nigeria faces significant security challenges due to the activities of terrorist groups like Boko Haram and ISWAP, resulting in violence, loss of lives, and socioeconomic disruption. Numerous deaths, large-scale displacement and social upheaval in the surrounding areas have been brought about by these organization acts of widespread violence. This paper highlights how vital it is to set up specialized anti-terrorism courts in order to successfully handle these critical problems. It emphasizes the shortcomings of the current legal systems in prosecuting terrorism-related offences by looking at the security environment today and the significant effects of insurgencies on national stability and governance. In order to address these concerns strategically, this paper examines the pressing need for specialized anti-terrorism courts. Through an examination of the state of community security and current legal affairs, it amplifies the shortcomings of the current legal systems in successfully prosecuting offences related to terrorism. Aiming to defend human rights, accelerate trials, and improve judicial efficiency all of which will increase public confidence in the legal system, dedicated courts should be established. This paper makes the case that anti-terrorist courts can handle particular legal issues about terrorism, enhance trial outcomes, and operate as a deterrence against further violence by referencing comparative legal frameworks and global best practices. Ultimately the establishment of these courts is necessary to bring about justice, restore peace, and bolster Nigeria's resolve to fight terrorism.